Interpretable machine learning for optimization of ultrasound-assisted polysaccharide extraction using natural deep eutectic solvents: From yield enhancement to structural and antioxidant activity validation - Shulu Zhang; Jingting Han; Ruichen Gao; Yeqing Xu; Zheng Feng; Xinhui Huang; Yinze Zhong; Qingxia Wang; Xinran Yu; Siyu Chang; Meiting Jiang; Zhibin Wang; et al. (Bioresource Technology, 2026)

Multistep generative backmapping of coarse-grained structures - Georgios Kementzidis; Erin Wong; John Nicholson; Ruichen Xu; Yuefan Deng (Computer Physics Communications, 2026)

Physics-Informed Deep-Learning Prediction of Tropical Cyclone Wind Size in the Western North Pacific - Ruichen Guo; Jing Xu; Chi Yang; Mingzhu Zhou (Journal of Meteorological Research, 2026)

Dataset of China Kuroshio Extension Observatory (CKEO): Moored Buoy Observations in the Kuroshio–Oyashio Transition Zone - Zhaohui Chen; Yueqi Zhang; Ruichen Zhu; Zhongxiang Fan; Jia-Zhen Wang; Xin Ma; Guoqing Ren; Haiyuan Yang; Lixiao Xu; Xiaopei Lin; Lixin Wu (Advances in Atmospheric Sciences, 2026)
The Kuroshio–Oyashio Transition Zone (KOTZ) serves as a vital dynamic interface between the warm Kuroshio Extension and the cold Oyashio Current. However, severe sea conditions with strong ocean currents, winds and waves pose challenges for sustained in situ observations of both oceanic and atmospheric variables. This paper introduces the China Kuroshio Extension Observatory (CKEO), a moored observatory program designed for long-term observations in the KOTZ. We provide a dataset of meteorological and oceanographic properties, including sea surface wind, air temperature, atmospheric pressure, relative humidity, sea surface temperature, sea surface salinity, ocean currents in the upper 100 m, and temperature profile in the upper 500 m. The CKEO, which began operations in 2019, provides a continuous air–sea observational dataset of the KOTZ to the scientific community and advances the understanding of multiscale physical processes in this region.

Vertical distribution of new and weathered microplastics in the water column: Implications for developing reliable sampling methods - Arghavan Beheshtimaal; Ruichen Xu; Binbin Wang; Maryam Salehi (Water Research, 2025)

In situ growth of ultrasmall MoO3 nanoparticles into 3D porous reduced graphene oxide for efficient oxidative desulfurization of high-sulfur - Peng Zuo; Xianping Chu; Fanfan Liu; Xu Cai; Ruichen Li; Yanbo Sun; Zhouqin Xu; Zhiwei Zhang; Yun Shen; Jinyun Liu; Yefeng Liu (Journal of Environmental Chemical Engineering, 2025)

Upcycling PET waste into carbon quantum dots as flame retardant of PET for closed-loop recycling - Jianfei Wei; Guocong Ma; Yaoyao Tang; Jing Zhang; Gaoling Jin; Chaohui Ma; Linhan Bing; Zhiguo Zhu; Zhenfeng Dong; Puzhen He; Ruichen Zhou; Rui Wang; et al. (Chemical Engineering Journal, 2025)

Discovering VEGFR-targeting constituents from Chloranthus holostegius guided by affinity screening - Wenhui Liu; Haojing Jiang; Xinxing Li; Ruichen Guo; Jing Xu; Yuanqiang Guo (Phytochemistry, 2025)

Self-templated fabrication of heterogeneous F doped NiCo-alkoxides/NiCo hydroxides yolk-shelled spheres with enhanced performance for supercapacitors - Xu Zhang; Ying Chen; Shuxian Song; Lu Song; Ruichen Zhai; Yulan Meng; Shaojie Li; Lijuan Wei; Xutong Yang; Anmin Liu (Chemical Engineering Journal, 2025)

Glycine as an effective electrolyte additive to improve the cycling performance of iron-chromium redox flow batteries - Wei Qiu; Tianhang Zhou; Ruichen Zhou; Runfa Zhao; Zhuohao Gao; Yizhong Yan; Chunming Xu; Quan Xu; Yingchun Niu (Chemical Engineering Journal, 2025)

Monthly variations of the spring greenness response across boreal Eurasia to the preceding wintertime northern annular mode during 1982–2022 - Jing Li; Weiming Zeng; Ruichen Lin; Zhiqing Xu; Xilin Xie; Feng Su; Rui Zhao; Anmin Duan (Climate Dynamics, 2025)

Oil Spill Occurrence and Pollution Risk Assessment Based on Sea State, Oil Platform Location, and Shipping Route Density in the Bohai Sea - Tao Liu; Ruichen Cao; Minxia Zhang; Xing Chen; Fan Bi; Jiangling Xu (Journal of Marine Science and Engineering, 2025)
The Bohai Sea is the only semi-enclosed inland sea in China. With active marine economic activities, it faces a persistently high risk of oil spill accidents. This study assesses the occurrence risk and pollution risk of oil spills by considering factors such as sea state, the location of oil platform, and shipping route density in the Bohai Sea. The results show that the central part of the Bohai Sea, the southern Liaodong Peninsula, and the Bohai Strait area have a relatively high occurrence risk of oil spills due to busy maritime traffic and harsh sea conditions. In contrast, some areas in the northern, western, and southern parts of the Bohai Sea have a relatively low occurrence risk of oil spills because of weak maritime activity intensity and relatively calm sea state. In terms of the oil pollution risk, its distribution in the Bohai Sea shows significant seasonal characteristics, which are mainly comprehensively affected by multiple dynamic factors such as circulation, monsoon, and seawater exchange. Based on the oil pollution risk distribution, seasonally targeted strategies are proposed, which can provide a scientific basis for oil spill prevention and emergency management in the Bohai Sea, and help relevant departments formulate targeted prevention and control strategies.

Nomogram to predict central lymph node metastasis in papillary thyroid carcinoma - Dehui Qiao; Xian Deng; Ruichen Liang; Xu Li; Rongjia Zhang; Zhi Lei; Hui Yang; Xiangyu Zhou (Clinical & Experimental Metastasis, 2024)

The effects of wind-wave disturbances on sediment resuspension and phosphate release in Lake Chao - Jingxian Wang; Jisen Chai; Ruichen Xu; Yong Pang (Science of The Total Environment, 2024)

With spatial distribution, risk evaluation of heavy metals and microplastics to emphasize the composite mechanism in hyporheic sediments of Beiluo River - Bingjie Li; Jinxi Song; Mingchang Guan; Zeyu Chen; Bin Tang; Yongqing Long; Ruichen Mao; Jiawei Zhao; Wenjin Xu; Yuting Zhang (Journal of Hazardous Materials, 2024)

Response of the runoff process to meteorological drought: Baseflow index as an important indicator - Ruichen Mao; Aying Shi; Jinxi Song; Wenjin Xu; Bin Tang; Bingjie Li (Journal of Environmental Management, 2023)

Analysis and simulation of the driving mechanism and ecological effects of land cover change in the Weihe River basin, China - Wenjin Xu; Jinxi Song; Yongqing Long; Ruichen Mao; Bin Tang; Bingjie Li (Journal of Environmental Management, 2023)

The liquefaction pressure characteristics of silty soil in the Chengdao area: Numerical simulations - Qixiang Wang; Yupeng Ren; Ruichen Cao; Guohui Xu; Xianqing Lv (Ocean Engineering, 2023)

Vegetation variation regulates soil moisture sensitivity to climate change on the Loess Plateau - Mao Ruichen; Song Jinxi; Tang Bin; Xu Wenjin; Kong Feihe; Sun Haotian; Lei Yuxin (Journal of Hydrology, 2023)

Pinocembrin Inhibits P2X4 Receptor–Mediated Pyroptosis in Hippocampus to Alleviate the Behaviours of Chronic Pain and Depression Comorbidity in Rats - Runan Yang; Jingjian Yang; Zijing Li; Ruichen Su; Lifang Zou; Lin Li; Xiumei Xu; Guilin Li; Shuangmei Liu; Shangdong Liang; Changshui Xu (Molecular Neurobiology, 2022)

Effects of different habitats on the bacterial community composition in the water and sediments of Lake Taihu, China - Wenjie Chang; Jieli Sun; Yong Pang; Songhe Zhang; Lixue Gong; Jiaang Lu; Bin Feng; Ruichen Xu (Environmental Science and Pollution Research, 2020)